2011
DOI: 10.1038/onc.2011.448
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β-catenin signaling by nongenomic action of orphan nuclear receptor Nur77

Abstract: Dysregulation of β-catenin turnover due to mutations of its regulatory proteins including APC and p53 is implicated in the pathogenesis of cancer. Thus, intensive effort is being made to search for alternative approaches to reduce abnormally activated β-catenin in cancer cells. Nur77, an orphan member of the nuclear receptor superfamily, plays a role in the growth and apoptosis of cancer cells. Here, we reported that Nur77 could inhibit transcriptional activity of β-catenin by inducing β-catenin degradation vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 60 publications
1
47
0
Order By: Relevance
“…In connection with the orphan receptors, it has been reported that Nur77, a related member of the orphan receptor family, possesses two NLSs and three NES signals that are implicated in its redistribution from the nucleus to the cytoplasm (44). Of note, it has been reported recently that Nur77 is exported from the nucleus by the exportin CRM1 (36). The presence of several regulatory signals may confer superior versatility to integrate alternative mechanisms of subcellular regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In connection with the orphan receptors, it has been reported that Nur77, a related member of the orphan receptor family, possesses two NLSs and three NES signals that are implicated in its redistribution from the nucleus to the cytoplasm (44). Of note, it has been reported recently that Nur77 is exported from the nucleus by the exportin CRM1 (36). The presence of several regulatory signals may confer superior versatility to integrate alternative mechanisms of subcellular regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with the results of previous studies with regard to the interplay between Nur77 and the Wnt/β-catenin signaling pathway in colon cancer cells and in osteoblasts. 20,21,31 This signaling crosstalk may help to identify potential therapeutic targets for vascular remodeling associated with RAS hyperactivation during hypertension, atherosclerosis, vascular injury, restenosis, and aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between Nur77 and the Wnt/β-catenin signaling pathway in cancer cells has been well reported in in vitro and in vivo settings. 20,21 Nur77 significantly suppresses Wnt/β-catenin activity via distinct mechanisms. 20,21 However, no direct information is available about the role of β-catenin in Ang II-induced vascular remodeling, and the mechanism by which β-catenin is regulated.…”
mentioning
confidence: 99%
“…In colon cancer cell lines, a bile acid carcinogen (deoxycholic acid) has been shown to stimulate b-catenin-dependent increased expression of NR4A1 (10). Conversely, NR4A1 has been shown to promote degradation of cytoplasmic b-catenin in a transcription-independent mechanism, whereas in murine models, NR4A1 has been shown to reduce tumor cell proliferation by transcriptional inhibition of Wnt signaling (11,12).…”
Section: Apoptosismentioning
confidence: 99%